Characteristics of important diploid and tetraploid subspecies of Dactylis from point of view of the forage crop production - V. Míka; A. Kohoutek; V. Odstrčilová (Plant, Soil and Environment, 2002)
Tetraploid ecotypes originated from Atlantic coastal region in comparison to diploids are of large growing stature, they build looser tuft (P0.95), fewer vegetative offshoots (P0.99). Their leaves are coarser (P0.99), culms are thicker (N.S.), less foliaged (P0.99), the thousand-seed-weight is higher (P0.99). They are in heading time earlier, generally more productive, the forage quality is good. From diploid subspecies, it is the ssp. aschersoniana, which adapted to the climatic condition of central Europe best and meets the requirements of herbage production. Ssp. galiciana proved to be also a high yielding grass, possessing higher resistance against rust, mildew, and good resistance against fusarioses. Ssp. lusitanica has smoother leaves, but it is less yielding, leaves proportion in herbage is lower, and shows lower winter hardness. It seems to be of little interest as a genetic resource for simple forage grass breeding in this country.